2007
DOI: 10.1016/s0929-6646(08)60060-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Response and Length of Stay for Inpatients with Major Depression

Abstract: There was no evidence to show that patients with a long hospital stay would gain treatment benefits over patients with short stay. This study provides evidence to support that a structured inpatient treatment plan might gain some economic benefits without compromising treatment efficacy. The admission of hospitalization repeaters should be managed optimally based on the considerations of treatment efficacy and its impact on longer hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
0
19
0
4
Order By: Relevance
“…42Y44 Adding to this knowledge base, we found that a previous suicide attempt was a strong predictor of poor response to antidepressant treatment even after adjusting for baseline characteristics associated with this history, including baseline severity of depression. A few studies have suggested that suicide attempts or ideation may predict relapse in depression, 45,46 but to our knowledge, ours is the first study to report a prospective association with poor treatment outcomes in a large prospective Asian cohort. A pharmacogenetic study with escitalopram and nortriptyline in the United Kingdom found that, contrary to our findings, a history of suicide attempts was not associated with differences in treatment responses.…”
Section: Discussionmentioning
confidence: 66%
“…42Y44 Adding to this knowledge base, we found that a previous suicide attempt was a strong predictor of poor response to antidepressant treatment even after adjusting for baseline characteristics associated with this history, including baseline severity of depression. A few studies have suggested that suicide attempts or ideation may predict relapse in depression, 45,46 but to our knowledge, ours is the first study to report a prospective association with poor treatment outcomes in a large prospective Asian cohort. A pharmacogenetic study with escitalopram and nortriptyline in the United Kingdom found that, contrary to our findings, a history of suicide attempts was not associated with differences in treatment responses.…”
Section: Discussionmentioning
confidence: 66%
“…Over the past several decades, the LOS for patients requiring psychiatric hospitalisation has decreased from months to weeks, driven not only by economic pressures but by advances in clinical practice with a focus on treatment in outpatient settings [1315]. There is some debate as to the optimum LOS in psychiatric patients; some studies argue that patients with depression who are discharged after a brief inpatient treatment are more depressed and more globally impaired on discharge [13], while other studies suggest that shorter stay is as effective or more effective than long-term inpatient programmes among depressed patients [16,17], or patients with severe mental illness [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Yaş, hastalık süresi, atak sayısı, başlangıç yaşı, ailede psikiyatrik hastalık hikayesi (özellikle depresyon), cinsiyet, medeni durum ve eğitim gibi sosyodemografik değişkenlerin AD tedaviye cevabı öngöremediklerini bildiren birçok çalışmada bulunmaktadır (11,31,35,51,55,56,57). Depresyonda AD tedaviye cevabı öngörebilmek için, hastaların sosyodemografik ve hastalık özelliklerini araştıran ve birbirleriyle çelişen çalışmalar arasında ortaya çıkan tutarsızlık, bu çalışmalarda kullanılan farklı çalışma desenlerine ve buna bağlı oluşan hasta gruplarına, denek sayısına, tercih edilen ilaç tedavilerine, takip süresine ve ölçüm araçlarına bağlı olabilir.…”
Section: Discussionunclassified
“…Literatür verisi çalışmamızda ulaşılan sonuç ile doğru orantılıdır. Kuvvetli sosyal desteği bulunan ve sosyoekonomik durumu iyi olan depresyon hastalarının AD tedaviden daha fazla yararlandıkları ifade edilmektedir ayrıca kuvvetli sosyal desteğin olumsuz yaşam olaylarının depresojenik etkisini tamponize ettiği de belirtilmektedir (34,42,57,60).…”
Section: Discussionunclassified